EFFECT OF FAT GRAFTING ON IMPROVEMENT OF SCAR-AN INTERVENTIONAL STUDY - Abdul Sattar, Sumaira; Faisal Akhlaq,; Waqas Sami,; Maryam Noor,; Farhan Zahid,; Unza Shaikh, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Scars are inevitable after effect of wound healing, a natural process that restores tissue integrity following injury, burns or surgery. They can be aesthetically displeasing and functionally impairing, depending on their location, size, and depth. Depending on the severity of the injury, scars can be hypertrophic, atrophic, or keloid. These variations can lead to pain, itching, contractures (limited movement), and psychological distress, impacting a patient's quality of life. Objective was to evaluate the efficacy of autologous fat grafting in improving the appearance and quality of scars, with a focus on patients presenting with facial scars due to burns, trauma, surgery or acne at a tertiary care hospital in Karachi, Pakistan. Methods: In this quasi-experimental study, 30 patients of age 18 years to 60 years, irrespective of gender having facial scar because of burn, trauma, surgery or acne were included in the study. A comprehensive scar assessment was performed using the Patient and Observer Scar Assessment Scale (POSAS) before treatment, and follow-up evaluations were conducted on the seventh day, at three months, and at six months post-fat grafting. Fat grafting was executed using a tumescent technique based on Klein's formula, with the aspirated fat injected into the subdermal plane of the scar. Data analysis was performed using SPSS version 23. Results: The patient cohort had a mean age of 26.77 years, with a predominance of female participants (73.3%). Trauma was the most common cause of scars (50%), with the forehead being the most frequent location (36.67%). Significant improvements in scar quality were observed, with both patient and observer POSAS scores showing notable reductions from baseline to 6 months (p<0.05). All patients (100%) demonstrated an improvement in scar appearance. Conclusion: Fat grafting presents a promising treatment for improving the appearance and quality of facial scars.